Ral small GTPase signaling and oncogenesis: more than just 15 minutes of fame - Gentry, Leanna R. (2014)
Since their discovery in 1986, Ral (Ras-like) GTPases have emerged as critical regulators of diverse cellular functions. Ral-selective guanine nucleotide exchange factors (RalGEFs) function as downstream effectors of the Ras oncoprotein, and the RalGEF-Ral signaling network comprises the third best characterized effector of Ras-dependent human oncogenesis. Because of this, Ral GTPases as well as their effectors are being explored as possible therapeutic targets in the treatment of RAS mutant cancer. The two Ral isoforms, RalA and RalB, interact with a variety of downstream effectors and have been found to play key and distinct roles in both normal and neoplastic cell physiology including regulation of vesicular trafficking, migration and invasion, tumor formation, metastasis, and gene expression. In this review we provide an overview of Ral biochemistry and biology, and we highlight recent discoveries.